2011
DOI: 10.1111/j.1744-6155.2011.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Care coordination for children with complex care needs significantly reduces hospital utilization

Abstract: Hospital utilization is significantly reduced for children with complex care needs through 24/7 care coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…Kuhlthau and colleagues (Kuhlthau et al, 2005) found finance-related problems were reduced when CSHCN received coordinated and ongoing comprehensive care in a medical home, had adequate private and/or public insurance, and had community-based service systems that were organized and easy to use. Many children with disability benefit from improved care coordination, which is also associated with reduced overall cost of care (Casey et al, 2011; Gordon et al, 2007; Liptak, Burns, Davidson, & McAnarney, 1998; Peter et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Kuhlthau and colleagues (Kuhlthau et al, 2005) found finance-related problems were reduced when CSHCN received coordinated and ongoing comprehensive care in a medical home, had adequate private and/or public insurance, and had community-based service systems that were organized and easy to use. Many children with disability benefit from improved care coordination, which is also associated with reduced overall cost of care (Casey et al, 2011; Gordon et al, 2007; Liptak, Burns, Davidson, & McAnarney, 1998; Peter et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…For many of these children, their reliance on technology demands a tailor-made service to ensure that care within the home is viable and sustainable [4]. Progress towards achievement of this goal has been slow [3] despite growing evidence that homecare: provides a means of mitigating the barriers and isolation children and their families experience during the transition from hospital to home, can significantly reduce hospital utilisation, and reduces the cost of care for children with complex care needs [56789]. …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of children with complex medical conditions has increased recently by four-fold (Raphael, Mei, Brousseau, & Giordano, 2011). Complex medical conditions constitute an increasing proportion of inpatient pediatric care and resource use (Peter et al, 2011;Simon et al, 2010). Engaging discharge planning resources early in the hospital stay maximize the time available to design and implement a complex discharge plan.…”
Section: Discussionmentioning
confidence: 99%